Phage-Borne Depolymerases Decrease Klebsiella pneumoniae Resistance to Innate Defense Mechanisms - Majkowska-Skrobek, Grazyna; Latka, Agnieszka; Berisio, Rita; Squeglia, Flavia; Maciejewska, Barbara; Briers, Yves; Drulis-Kawa, Zuzanna (Frontiers in Microbiology, 2018)
Klebsiella pneumoniae produces capsular polysaccharides that are a crucial virulence factor protecting bacteria against innate response mechanisms of the infected host. Simultaneously, those capsules are targeted by specific bacteriophages equipped with virion-associated depolymerases able to recognize and degrade these polysaccharides. We show that Klebsiella phage KP32 produces two capsule depolymerases, KP32gp37 and KP32gp38, with a high specificity for the capsular serotypes K3 and K21, respectively. Together, they determine the host spectrum of bacteriophage KP32, which is limited to strains with serotype K3 and K21. Both depolymerases form a trimeric β-structure, display moderate thermostability and function optimally under neutral to alkaline conditions. We show that both depolymerases strongly affect the virulence of K. pneumoniae with the corresponding K3 and K21 capsular serotypes. Capsule degradation renders the otherwise serum-resistant cells more prone to complement-mediated killing with up to two log reduction in serum upon exposure to KP32gp37. Decapsulated strains are also sensitized for phagocytosis with a two-fold increased uptake. In addition, the intracellular survival of phagocytized cells in macrophages was significantly reduced when bacteria were previously exposed to the capsule depolymerases. Finally, depolymerase application considerably increases the lifespan of Galleria melonella larvae infected with K. pneumoniae in a time- and strain-dependent manner. In sum, capsule depolymerases are promising antivirulence compounds that act by defeating a major resistance mechanism of K. pneumoniae against the innate immunity.